Analisis Strategi Pemasaran Beras Betet pada Toko Cenderawasih Fakfak - Maria Wesso; Agustina Waromi (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2026)
This study aims to analyze the marketing strategy of Betet Rice at Toko Cendrawasi Fakfak. The research uses a qualitative approach with data collection methods including field research, interviews with managers and employees, observations on sales data management, and documentation. The data were analyzed using marketing mix analysis and SWOT analysis. The results show that Betet Rice is distributed directly to customers through Toko Cendrawasi Fakfak, which acts as a distributor of the product. Toko Cendrawasi has made efforts to provide significant market access for Betet Rice marketing, with products and prices adjusted to customer desires and purchasing power. The marketing strategy used involves the marketing mix of product, price, promotion, and distribution, which has led to an increase in demand for Betet Rice every year. Based on the SWOT analysis, the marketing strategy implemented includes strengths in strong financial conditions and a fleet of ships, weaknesses in the lack of attention to key marketing elements, opportunities in market analysis and customer segmentation, and threats from increasing competition and globalization of competitors offering similar products.